Layanan Konseling Individual untuk Mengatasi Kecemasan dan Ketegangan pada Siswa dengan Teknik Relaksasi Otot Kelas IX di SMP Negeri 4 Aimere (Universitas Negeri Makassar, 2022)
The purpose of this study were (1) to determine the types of anxiety a experienced by students, (2) factors that cause anxiety asiswa, (3) counseling approach applied Teacher BK inovercoming the anxiety of students, and (4) to know the assessment of students to counseling services that do counseling teacher at the school as perceived by the counseling teacher at the school. This research is qualitative obtained from the informant and the subject's behavior is observed. Instruments are students and teachers BK with a sample size 3 students and 1 teachers BK SMP NEGERI 4 AIMERE Data collection through direct interview to the informant. The results showed that (1) the types of anxiety experienced by students who studied are anxiety is psychological in the form of dizziness, anxiety, and could not sleep, (2) factors that cause anxiety students are learning achievement that is not in line with expectations, could not adjust to the subject, had no educational aspirations, and worried about the future, (3) a tutor in overcoming anxiety academic in students, not using the obvious approach in dealing swith students who have anxiety problems of academic, approach still partial, incidental routines, and tend to be behavioristik, (4) counseling service approach used by teachers in handling anxiety BK students have not been effective, both in the eyes of students and teachers BK itself.so that the BK teacher conduct individual counseling by using the relaxation techniques